What do we know about blood-testis barrier? current understanding of its structure and physiology - Luaces, J. P.; Toro-Urrego, N.; Otero-Losada, M.; Capani, F. (Frontiers in Cell and Developmental Biology, 2023)
Blood-testis barrier (BTB) creates a particular compartment in the seminiferous epithelium. Contacting Sertoli cell-Sertoli cell plasma membranes possess specialized junction proteins which present a complex dynamic of formation and dismantling. Thus, these specialized structures facilitate germ cell movement across the BTB. Junctions are constantly rearranged during spermatogenesis while the BTB preserves its barrier function. Imaging methods are essential to studying the dynamic of this sophisticated structure in order to understand its functional morphology. Isolated Sertoli cell cultures cannot represent the multiple interactions of the seminiferous epithelium and in situ studies became a fundamental approach to analyze BTB dynamics. In this review, we discuss the contributions of high-resolution microscopy studies to enlarge the body of morphofunctional data to understand the biology of the BTB as a dynamic structure. The first morphological evidence of the BTB was based on a fine structure of the junctions, which was resolved with Transmission Electron Microscopy. The use of conventional Fluorescent Light Microscopy to examine labelled molecules emerged as a fundamental technique for elucidating the precise protein localization at the BTB. Then laser-scanning confocal microscopy allowed the study of three-dimensional structures and complexes at the seminiferous epithelium. Several junction proteins, like the transmembrane, scaffold and signaling proteins, were identified in the testis using traditional animal models. BTB morphology was analyzed in different physiological conditions as the spermatocyte movement during meiosis, testis development, and seasonal spermatogenesis, but also structural elements, proteins, and BTB permeability were studied. Under pathological, pharmacological, or pollutant/ toxic [5] conditions, there are significant studies that provide high-resolution images which help to understand the dynamic of the BTB. Notwithstanding the advances, further research using new technologies is required to gain information on the BTB. Super-resolution light microscopy is needed to provide new research with high-quality images of targeted molecules at a nanometer-scale resolution. Finally, we highlight research areas that warrant future studies, pinpointing new microscopy approaches and helping to improve our ability to understand this barrier complexity.